2020
DOI: 10.3390/ma14010077
|View full text |Cite
|
Sign up to set email alerts
|

DFT Study of MAX Phase Surfaces for Electrocatalyst Support Materials in Hydrogen Fuel Cells

Abstract: In moving towards a greener global energy supply, hydrogen fuel cells are expected to play an increasingly significant role. New catalyst support materials are being sought with increased durability. MAX phases show promise as support materials due to their unique properties. The layered structure gives rise to various potential (001) surfaces. DFT is used to determine the most stable (001) surface terminations of Ti2AlC, Ti3AlC2 and Ti3SiC2. The electrical resistivities calculated using BoltzTraP2 show good a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…The DOS and band structure results agree with previous works on theoretical studies of Nb 2 AlC, 57,58 Ta 2 AlC 36 and Ti 3 AlC 2 . 35,59 Having a basic understanding of the MAX, we proceeded with extensive experimental material characterisations. SEM was used to study the morphology of the three phases and the obtained micrographs are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The DOS and band structure results agree with previous works on theoretical studies of Nb 2 AlC, 57,58 Ta 2 AlC 36 and Ti 3 AlC 2 . 35,59 Having a basic understanding of the MAX, we proceeded with extensive experimental material characterisations. SEM was used to study the morphology of the three phases and the obtained micrographs are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The DOS and band structure results agree with previous works on theoretical studies of Nb 2 AlC, 57,58 Ta 2 AlC 36 and Ti 3 AlC 2 . 35,59…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was also reported elsewhere that the stoichiometric (100) surface is the most stable, and additionally that the Al terminated (110) surface becomes more stable as the Al chemical potential increases [13]. Gertzen et al [14] employed the DFT method to investigate MAX phase surfaces of (Ti2AlC, Ti3AlC2 and Ti3SiC) for electrocatalyst support material in hydrogen fuel cells. It was reported that the cleavage energy value for Ti2AlC is lower (1.924 to 5.254 eV/unit cell) than Ti3AlC2 (1.9-6.48 eV/unit cell) and Ti3SiC2 (2.8-6.47 eV/unit cell) surfaces.…”
Section: Introductionmentioning
confidence: 98%
“…The MAX phases are ternary transition metal carbide and/or nitride with a layered hexagonal crystal structure [26,27]. The unique structure endows them the dual properties of both metals and ceramics, that is, they are machinable and possess high electronic conductivities, are lightweight, and oxidation resistant [28,29]. Further studies by Ng et al showed the potential of Ti 3 AlC 2 as a catalyst in selective oxidation reactions, which was most likely derived from the non-stoichiometric oxide surface layer containing oxygen vacancies [30].…”
Section: Introductionmentioning
confidence: 99%